Evaluation of artistic installations in urban spaces in Kosovo - Muharremi, Ilir Hivzi; Muharremi, Merita (Street Art & Urban Creativity, 2024)
This paper deals with the art of installations in urban spaces in Kosovo. Evaluation of installations as art in relation to public spaces. How much do you decorate these spaces? How much does this art lose the value of architecture? Whether installations in public places in Kosovo have a real value? The paper is made on these research questions, resulting in the fact that the installations of famous Kosovar artists express personal, social and real themes of the time.